The earliest Christian heretics readings from their opponents - Hultgren, Arland J.; Haggmark, Steven A. (Minneapolis, MN Fortress, 1996)
Includes bibliographical references and index.
Keywords: Heresies, Christian -- early Works to 180.; Heretics, Christian -- early Works to 180.; Christian literature, Early